P68 Time-course Of Human Rhinovirus Infection And Upper Respiratory Tract Symptoms During Copd Exacerbations. (10th November 2014) - George, SN; Brill, SE; Allinson, JP; Singh, R; Kowlessar, B; Sapsford, RJ; Donaldson, GC; Wedzicha, JA
Abstract : Introduction: Human rhinoviruses (HRV) are the main aetiological agents of virus-associated COPD exacerbations (Seemungal et al . AJRCCM 2001). The relationship between upper respiratory tract symptoms and HRV load at exacerbation presentation (ExP) and during recovery has not been described in naturally-occurring exacerbations. We quantified changes in airway HRV load at ExP and during the recovery period, in patients reporting symptoms of a cold, sore throat, or both. Methods: Patients in the London COPD cohort recorded new or increased respiratory symptoms on daily diary cards. Exacerbations were defined as an increase in respiratory symptoms for two consecutive days, with at least one symptom being major (dyspnoea, sputum purulence or volume) and the other a major or minor (wheeze, cold, sore throat, cough). Reverse-transcription quantitative PCR was used to detect and quantify HRV in 106 sputum samples collected at ExP (n = 38) and days 3 (n = 16), 7 (n = 27), 14 (n = 16), 35 (n = 6) and 56 (n = 3) following. Results: HRV load decreased significantly from ExP to Day 3 in samples associated with either cold symptoms (p < 0.001) or sore throat (p = 0.049) but not in those associated with both symptoms (Figure 1). At Day 3 the HRV load in samples with both symptoms (n = 5) was significantly higher than in those with cold symptoms only (n = 9) (10 4.22(3.94–4.88) vs 10 0.55(0–1.98) pfu/ml; p = 0.002) but not for those with a sore throat only (n = 2) (10 0.89(0–0.89) pfu/ml; p = 0.095). At Day 7, the median (IQR) HRV load in samples with both symptoms (n = 4) (10 4.48(1.85–7.28) pfu/ml) was significantly higher than in those with cold symptoms only (n = 19) (10 0(0–2.74) pfu/ml; p = 0.018) or a sore throat only (n = 4) (10 0(0–0) pfu/ml; p = 0.029). There was no significant difference at subsequent time-points. Conclusion: Patients reporting both cold symptoms and a sore throat as part of a COPD exacerbation had higher HRV loads than those with just one symptom until after Day 7 post-exacerbation. In patients with both symptoms, the HRV load remained higher for a longer period of time than in patients with only one symptom, which may suggest longer recovery times for more symptomatic patients. These results may inform the timing of administration of antiviral therapies at COPD exacerbation.